2011
DOI: 10.3342/ceo.2011.4.2.67
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EGFR and Microvessel Density in Middle Ear Cholesteatoma

Abstract: ObjectivesCholesteatoma destructs bony tissue by the interactions between hyperproliferative epithelial cells and subepithelial inflammatory cells. The aim of this study was to evaluate the expression of epidermal growth factor receptor (EGFR) and microvessel density (MVD) in middle ear cholesteatoma tissue in an effort to determine the relationship between expression of EGFR and neovascularization.MethodsWe evaluated the expression of EGFR and MVD by immunohistochemical staining for CD31 and Factor VIII in 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…The link between EGFR and MVD was studied in several human tumours (Perrotte et al, 1999;Baumann and Krause, 2004;Iivanainen et al, 2009;Diaz et al, 2010;Jin et al, 2011), including breast cancer (Fox et al, 1994;Weidner and Gasparini, 1994;Nieto et al, 2007;Nickerson et al, 2012). In CMT, MVD accessed by CD31 immunoexpression was studied by some authors (Graham and Myers, 1999;Restucci et al, 2000;Lavalle et al, 2009;Queiroga et al, 2011), and EGFR immunoexpression was also described (Gama et al, 2009;Guimarães et al, 2013;Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The link between EGFR and MVD was studied in several human tumours (Perrotte et al, 1999;Baumann and Krause, 2004;Iivanainen et al, 2009;Diaz et al, 2010;Jin et al, 2011), including breast cancer (Fox et al, 1994;Weidner and Gasparini, 1994;Nieto et al, 2007;Nickerson et al, 2012). In CMT, MVD accessed by CD31 immunoexpression was studied by some authors (Graham and Myers, 1999;Restucci et al, 2000;Lavalle et al, 2009;Queiroga et al, 2011), and EGFR immunoexpression was also described (Gama et al, 2009;Guimarães et al, 2013;Kim et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…[4][5][6][7][8][9] The most potent angiogenic factors are VEGF, IL-8, and cyclooxygenase 2 (COX-2) under inflammatory conditions in the middle ear.…”
mentioning
confidence: 99%
“…Therefore, increased CD-31 immunopositivity and the number of microvessels were accepted to be biological markers of chelesteatoma activity. Dornelles et al compared 60 pediatric and 60 adult patients in their study and they found the density of CD-31 as 7 (4)(5)(6)(7)(8)(9)(10)(11) in the pediatric patient group and as 4 (0-10) in the adult patient group (5). They evaluated this difference to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Jin et al on epidermal growth factor receptor and CD-31 levels, 32 cholesteatoma tissues were compared to 6 postauricular skin tissues (6). Epidermal growth factor receptor was found to be higher in cholesteatoma tissue, although it was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation